Chemical fingerprints, antioxidant, enzyme inhibitory, and cell assays of three extracts obtained from Sideritis ozturkii Aytaç & Aksoy: An endemic plant from Turkey - Zengin, Gokhan; Uğurlu, Asli; Baloglu, Mehmet Cengiz; Diuzheva, Alina; Jekő, József; Cziáky, Zoltán; Ceylan, Ramazan; Aktumsek, Abdurrahman; Picot-Allain, Carene Marie Nancy; Fawzi Mahomoodally, M (Elsevier BV, 2019)
This study was geared towards assessing the possible antioxidant, enzyme inhibitory, and cytotoxic activities of ethyl acetate, methanol, and water extracts of Sideritis ozturkii Aytaç & Aksoy. The phytochemical profiles of the studied extracts were characterised by HPLC-MS/MS. The methanol extract, rich in phenolics (78.04 mg gallic acid equivalent/g), exhibited the strongest antioxidant activities. However, the ethyl acetate extract was the most active extract in the enzyme inhibitory assays. The water extract of S. ozturkii (1 mg/ml, 48 h incubation) slightly inhibited (22%) growth of human breast cancer cell line (MDA-MB-231 cells). On the other hand, the ethyl acetate and methanol extracts showed strong inhibition (98% and 97%, respectively) of MDA-MB-231 cells and caused apoptotic cell death. Scientific data generated from this study further appraises the multiple biological activities of plants belonging to the Sideritis genus. In addition, preliminary evidence gathered from the current investigation advocates for further studies geared towards the preparation of therapeutic formulations from S. ozturkii.
Keywords: Turkey; Cell Survival; Plant Extracts; Methanol; Water; Acetates; Antineoplastic Agents, Phytogenic; Antioxidants; Cell Line, Tumor; Solvents; Humans; Sideritis; Enzyme Inhibitors